Profile of Children with Food Allergies at Dr. Soetomo Surabaya - Widodo, Naufallutfi; Endaryanto, Anang; Lestari, Pudji (Rifa'Institute, 2024)
Introduction: The rising prevalence of food allergies in both developed and developing countries has emerged as a significant public health concern. Food allergies can result from various foods, with common triggers in children including cow's milk, eggs, soy, wheat, fish, seafood, peanuts, tree nuts, and other dietary staples. These allergies can lead to diverse clinical manifestations affecting multiple organs and systems, posing severe health challenges, particularly for children. Objective: This study aims to outline the characteristics of pediatric patients with food allergies treated at Dr. Soetomo Hospital, Surabaya. Methods: A descriptive observational approach using a cross-sectional method was employed, analyzing data from patient medical records. The sample consisted of total cases meeting inclusion criteria. Results and Discussion: Among the patients, 61.1% were female, with an average age of 6.07 ± 3.44 years. Common allergenic foods included bananas (70.4%), tilapia fish (68.5%), and mackarel tuna (59.3%). Notably, 57.4% of children exhibited sensitivity to two or more allergen groups. The predominant clinical symptoms were rhinitis (92.6%) and chronic recurrent cough (70.4%). Conclusion: Pediatric food allergy patients are predominantly female, around six years old on average, with bananas, tilapia, and mackarel tuna identified as frequent allergens. Respiratory symptoms, particularly rhinitis and chronic cough, were the most common clinical presentations